The Influence of the Waste Bank Program on Nutritional Fulfillment of Households in Belawan II - Josua Hermanto Siregar; Alfiqri Bukhori; Khairul Azmi; Hulu, Weli Yusliani; Lubis, Rizal Paruhuman (International Journal of Economics, Commerce, and Management, 2025)
This study discusses the influence of the waste bank program on fulfilling household nutrition in Belawan II. In this context, the problem of child nutrition is a major challenge, especially in urban areas with low economic levels. Medan Belawan District faces nutritional problems due to limited access to nutritious food and low community income, which often hinders the fulfillment of balanced nutrition for children and other vulnerable groups. In addition, this study also highlights the relationship between waste problems and child nutrition, where suboptimal waste management has a negative impact on environmental health and the quality of life of the community. This has the potential to hinder the growth and development of children who should get adequate nutritional intake. The waste bank program is expected to increase family income through better waste management, which in turn can improve access and quality of food consumed by households. Thus, this program not only functions as a solution to waste management, but also as an intervention that supports improving household nutrition in the community. This study uses a descriptive qualitative approach to describe the presence of the digital waste bank movement as a digital-based environmental movemen that can have a positive impact on fulfilling household nutrition in Belawan II, especially amidst the challenges faced during the pandemic.